2017
DOI: 10.1039/c6mb00596a
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of circulating cytokines and microRNAs in lean and obese individuals with prediabetes and type 2 diabetes

Abstract: Today obesity and type 2 diabetes (T2D) have both reached epidemic proportions. However, our current understanding of the primary mechanisms leading to these diseases is still limited due to the complex multifactorial nature of the underlying phenomena. We hypothesize that the levels of specific cytokines and miRNAs vary across the diabetes spectrum and unique signatures associated with them may serve as early biomarkers of the disease and provide insights into respective pathogenetic mechanisms. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 51 publications
12
65
1
Order By: Relevance
“…Additionally, all but five participants had a waist circumference greater than 88 cm (risk criteria for MetS). In a study of lean and obese individuals with and without diabetes, Nunez Lopez et al () found positive correlations between percent body fat and both ci‐miR‐126 and ci‐miR‐146a, although we did not observe significant correlations with any ci‐miRs. Thus, a future study in a similar cohort to ours including a greater range of body fat levels may be needed to explore the relationship between body fat and cardiovascular ci‐miRs.…”
Section: Discussioncontrasting
confidence: 93%
“…Additionally, all but five participants had a waist circumference greater than 88 cm (risk criteria for MetS). In a study of lean and obese individuals with and without diabetes, Nunez Lopez et al () found positive correlations between percent body fat and both ci‐miR‐126 and ci‐miR‐146a, although we did not observe significant correlations with any ci‐miRs. Thus, a future study in a similar cohort to ours including a greater range of body fat levels may be needed to explore the relationship between body fat and cardiovascular ci‐miRs.…”
Section: Discussioncontrasting
confidence: 93%
“…Thus, in order to determinate the physiological stressors that could be affecting the relative expression of miR‐146a, miR‐34a, and miR‐375, we performed a detailed univariate analysis. We observed that the expression of miR‐146a was diminished in pre‐diabetic individuals, which is consistent with previous studies . Also, miR‐146a relative expression was associated with C‐reactive protein (an inflammatory marker) only in the T2D patients’ group.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have uncovered that loss of myeloid-miR-223 enhances diet-induced obesity and T2D utilizing mouse models (14,15). In addition, altered miR-223 levels in humans are associated with the advancement of obesity and T2D (16)(17)(18). Our current studies have established that KLF6 directly represses miR-223 expression to advance macrophage proinflammatory gene expression and attendant functions.…”
Section: Discussionmentioning
confidence: 55%
“…Deficiency of miR-223 is known to enhance proinflammatory macrophage activation and pathogenic functions (13)(14)(15). Recent human studies have uncovered that obesity and T2D status significantly altered miR-223 expression (16)(17)(18)(19). More importantly, macrophage miR-223 deficiency significantly elevated high-fat diet (HFD)-induced metabolic tissue inflammation, obesity, and T2D (14,15).…”
mentioning
confidence: 99%